European Foreign Policy in a Decarbonising World Challenges and Opportunities - Oberthür, Sebastian (Routledge Studies in Environmental Policy, 2022)
Contributing to the emerging literature on the geopolitical and foreign policy implications of decarbonisation and energy transition processes, this book sheds light on the future of the European Union's external relations under decarbonisation. Under the Paris Agreement on climate change, adopted in 2015, governments committed to phasing out the emissions of carbon dioxide and other greenhouse gases over the coming decades. This book addresses the many questions around this process of decarbonisation through detailed analyses of EU external relations with six fossil-fuel exporting countries: Nigeria, Indonesia, Azerbaijan, Colombia, Qatar and Canada. The authors systematically examine the six countries' varying dependence on fossil fuels, the broader political and security context, current relations with the EU and the potential for developing these toward decarbonisation. In doing so, they put forward a series of findings that should hold across varying circumstances and provide a steppingstone to enrich and inspire further research on foreign policy, external relations and international relations under decarbonisation. The book also makes an important contribution to understanding the external implications of the 2019 European Green Deal. This volume will be of great interest to students and scholars of European environmental and climate policy, climate diplomacy, energy policy, foreign policy and climate/energy geopolitics.